Longer and more frequent marine heatwaves over the past century - Eric C. J. Oliver (Nature Portfolio, 2018)
Marine heatwaves are climatic extremes with devastating and long-term impacts on marine ecosystems, fisheries and aquaculture. Here the authors use a range of ocean temperature observations to identify significant increases in marine heatwaves over the past century.